Geopolitics of Power Shifts: Analyzing Hay'at Tahrir al-Sham's Victory Over Assad and the Humanitarian Crisis in Syria - Bangkit Adi Saputra (Dialogia, 2025)
This study examines the factors contributing to Hay’at Tahrir al-Sham’s (HTS) military success against the Bashar al-Assad regime and analyzes the subsequent humanitarian governance challenges faced by HTS-led interim authorities in Syria. Employing a qualitative methodology grounded in historical and geopolitical analysis, the research utilizes library-based data to assess: (1) HTS’s effective guerrilla warfare strategies, (2) the impact of external actor involvement (particularly Turkey’s support for HTS versus diminished Russian or Iranian backing for Assad), and (3) the socioeconomic consequences of prolonged conflict. Findings reveal that HTS’s ascendancy stems from tactical military proficiency combined with the Assad regime’s weakening under Western sanctions and reduced support from traditional allies (Russia, Iran, Hezbollah, and the Houthis). However, the group’s political consolidation has exacerbated Syria’s preexisting humanitarian crisis, with interim governance structures proving inadequate to address postwar displacement, infrastructure collapse, and international isolation. The study concludes by emphasizing the urgent need for coordinated international engagement to: (a) mitigate large-scale human suffering, and (b) develop conflict-sensitive governance frameworks that account for Syria’s complex geopolitical realities. These insights contribute to broader discussions on non-state actor transitions to governance and humanitarian management in contested states. REFERENCES Abdussamad, Zuchri. Metode Penelitian Kualitatif. Edited by Patta Rapanna. Vol. 1. CV. Syakir Media Press, 2021. Al-Assad, Bashar. “Syria’s President Speaks: A Conversation with Bashar al-Assad.” Foreign Affairs 94, no. 2 (2015): 58–65. https://www.jstor.org/stable/24483482. Anggun Abadi, Fany, Ali Muhammad, and Takdir Ali Mukti. “Konflik Bersenjata di Idlib: Pertarungan Antar-Kepentingan Nasional.” Jurnal ICMES 6, no. 2 (December 2022): 166–81. https://doi.org/Doi.org/10.35748/jurnalicmes.v6i2.130. Armed Conflict Location & Event Data Project. “Hayat Tahrir Al-Sham (HTS) Actor Profile,” June 26, 2023. https://about.jstor.org/terms. ———. “Regional Overview Middle East April 2024,” May 10, 2024. https://www.jstor.org/stable/resrep59839. ———. “Regional Overview Middle East May 2023,” June 8, 2023. https://about.jstor.org/terms. ———. “Regional Overview Middle East May 2024,” June 10, 2024. https://about.jstor.org/terms. ———. “Syria: Which Groups Have Been Fighting Each Other and Where?,” December 11, 2024. https://www.jstor.org/stable/resrep65596. Azizi, Hamidreza, and Julien Barnes-Dacey. “Beyond Proxies: Iran’s Deeper Strategy In Syria And Lebanon,” June 2024. https://www.jstor.org/stable/resrep60706. Bahaudin Mudore, Syarif, N Mahasiswa, Pps Uin, and Sunan Kali. “Dinamika Perang Suriah: Aktor Dan Kepentingan.” POLITEA : Jurnal Kajian Politik Islam 2, no. 2 (December 2019): 67–92. Bank, Andre, and Ronja Herrschner. “Syria Is Not Safe: A Look to Its Regions,” August 2024. https://doi.org/10.57671/gfme-24052. Bryantr, Rebecca, Maissam Nimer, Aysen Ustubici, and Amal Abdulla. “Chapter Title: Conclusion. Growing Up and Moving On.” In Lives in Limbo: Syrian Youth in Turkey, 150–56. Berghahn Books, 2024. https://doi.org/10.3167/9781805395126. Cafarella, Jennifer, and Jason Zhou. “Report Part Title: Russia, Iran, and Assad Report Title: RUSSIA’S DEAD-END DIPLOMACY IN SYRIA,” November 2019. http://www.jstor.com/stable/resrep19570.5. Chatty, Dawn. “Chapter Title: Refuge in Syria: Where Duty Outweighs Human Rights-Based Approaches.” In Urban Displacement, edited by Are John Knudsen and Sarah A Tobin, 1st ed., 214–32. Berghahn Books, 2024. https://www.jstor.org/stable/jj.9891587.14. Czarkowska, Ewa, and Magdalena Kumelska-Koniecko. “Iran-Russia-Türkiye Triangle.” Source: Insight Turkey 25, no. 3 (2023): 199–222. https://doi.org/10.2307/48744767. Fakhry Ghafur, Muhammad. “Problems Of The Power Of Political Islam In Yemen, Syria And Algeria.” Jurnal Penelitian Politik 12, no. 2 (October 25, 2015): 119–35. www.republika.co.id/berita/dunia-islam/khazanah/15/04/30/. Fatmawati, Fatmawati. “Perubahan Politik Luar Negeri Rusia Terhadap Suriah Dalam Konflik Internal Suriah (2011–2017).” JDP (Jurnal Dinamika Pemerintahan) 3, no. 1 (February 3, 2020): 23–41. https://doi.org/10.36341/jdp.v3i1.1192. Hafidz, Danar, Adi Wardhana, Achmad Fauzi Kusmin, Muhammad Sajidin, Dewi Nuraliah, Nurfadilah Nasiruddin, and Rezky Ramadhan Antuli. “Keterlibatan Amerika Serikat Dalam Konflik Suriah Sebagai Konsekuensi Dari Politik Engtangling Alliance.” Arajang : Jurnal Ilmu Sosial Politik 6, no. 1 (2023): 22–38. https://doi.org/10.31605/arajang.v4i1. Hamidi, Ibrahim. “Source: Horizons: Journal of International Relations and Sustainable Development.” Horizons: Journal of International Relations and Sustainable Development 2024, no. 25 (2024): 10–19. https://doi.org/10.2307/48761177. Hauch, Lars, and Erwin Van Veen. “How the Aid Fund for Northern Syria Can Upgrade Humanitarian Aid and EU Geopolitical Engagement,” April 2024. https://www.unocha.org/publications/report/. International Crisis Group. “Report Part Title: Containing Transnational Jihadist Groups in Idlib Report Title: Containing Transnational Jihadists in Syria’s North West,” March 7, 2023. https://www.jstor.org/stable/resrep47445.8. ———. “Report Part Title: HTS versus ISIS Report Title: Containing Transnational Jihadists in Syria’s North West,” March 7, 2023. https://www.jstor.org/stable/resrep47445.7. ———. “Report Part Title: Idlib as Safe Haven and Holding Pen Report Title: Containing Transnational Jihadists in Syria’s North West,” March 7, 2023. https://www.jstor.org/stable/resrep47445.5. ———. “Report Part Title: Shades of Jihadism in Idlib Report Title: Containing Transnational Jihadists in Syria’s North West,” March 7, 2023. https://www.jstor.org/stable/resrep47445.6. ———. “Report Part Title: The HTS Conundrum Report Title: Silencing the Guns in Syria’s Idlib,” May 15, 2020. https://about.jstor.org/terms. Irdayanti, Irdayanti. “Kebijakan Penolakan Rusia Terhadap Strategi Barat Di Suriah.” Jurnal Pemikiran Islam 37, no. 2 (2012): 154–62. https://ejournal.uin-suska.ac.id/index.php/Anida/article/viewFile/323/306. Irfanullah, Gumilar, Dewi Anggraeni, Uin K H Abdurrahman, and Wahid Pekalongan. “Al-Fariq Ad-Dini Asy-Syababi As-Suri: Kristalisasi Sejarah Panjang Kebijakan Keagamaan Suriah Dan Perannya Pasca Perang Sipil Suriah.” Jurnal Tamaddun: Jurnal Sejarah Dan Kebudayaan Islam. Vol. 12, 2024. https://www.syekhnurjati.ac.id/jurnal/index.php/tamaddun/index. Jahanbani, Nakissa, and Suzanne Weedon Levy. “Report Part Title: Background on Iranian Proxy Involvement in Syria Report Title: Iran Entangled: Report Subtitle: Iran and Hezbollah’s Support to Proxies Operating in Syria,” April 2022. https://www.jstor.org/stable/resrep40421.6. Kusumastuti, Dita Arum. “Alasan Rusia Melibatkan Diri dalam Konflik Bersenjata Suriah Tahun 2011-2015.” Journal of International Relations 3, no. 4 (2017): 143–50. http://ejournal-s1.undip.ac.id/index.php/jihi. Martínez, José Ciro, and Brent Eng. “Stifling Stateness: The Assad Regime’s Campaign against Rebel Governance.” Security Dialogue 49, no. 4 (August 1, 2018): 235–53. https://doi.org/10.1177/0967010618768622. Masud, Muhammad. “Authoritarian Claims to Legitimacy: Syria’s Education under the Regime of Bashar al-Assad.” Mediterranean Studies 26, no. 1 (2018): 80–111. https://doi.org/10.5325/mediterraneanstu.26.1.0080. Menshawy, Mustafa. “Constructing State, Territory, and Sovereignty in the Syrian Conflict.” Politics 39, no. 3 (August 1, 2019): 332–46. https://doi.org/10.1177/0263395718770348. Nasution, Abdul Fattah. Metode Penelitian Kualitatif. Edited by Meyniar Albina. 1st ed. Vol. 1. Bandung: CV. Harfa Creative, 2023. Rabinovich, Itamar. “Iran’s Quest for Regional Hegemony.” Source: Horizons: Journal of International Relations and Sustainable Development, no. 26 (2024): 92–101. https://doi.org/10.2307/48790022. Rojhelati, Ziryan. “Post-Assad Syria: What the Fall of the Regime Means for the World,” December 8, 2024. https://about.jstor.org/terms. Sarmini, Mohammed. “Syria’s Political Stalemate.” Source: Insight Turkey 26, no. 2 (2024): 45–56. https://doi.org/10.2307/48778416. Syuryansyah, Syuryansyah. “Intervensi Militer Amerika Serikat Dalam Konflik Suriah Tahun 2011.” TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman 9, no. 2 (December 2023): 206–22. https://doi.org/10.24952/tazkir.v9i2.8851. Turki, Prince H .R.H. Al Faisal. “Global Uncertainties (What Lies Ahead in the Middle East).” Horizons: Journal of International Relations and Sustainable Development 2024, no. 26 (2024): 12–23. https://doi.org/10.2307/48790015. Valensi, Carmit, Raz Zimmt, and Gallia Lindenstrauss. “The Rebel Offensive in Syria: Strategic Shift or Fleeting Incident?,” December 4, 2024. https://about.jstor.org/terms. Veen, Erwin Van, and Olivia Macharis. “Clingendael Institute Hope Springs Eternal: EU Options for Dealing with the Assad Regime,” March 2020. http://www.jstor.com/stable/resrep24650. Winter, Ofir. “A Pivotal Player: Jordan and the New Syria,” January 12, 2025. https://www.jstor.org/stable/resrep66544.